Optimizing Learning Technology to Improve Literacy Habits in Indonesian Rural Schools - Harmita Sari; Rahmat Kamaruddin; Andi Nurhayati; Altri Wahida; Samsinar Samsinar; Dedi Aco (Universitas Negeri Makassar, 2026)
Technology learning has become an integral part of contemporary education and has a significant impact on students' writing literacy motivation. This study aims to review the level of motivation for writing literacy in Junior High Schools (SMP) in rural areas of Indonesia. In addition, this study aims to review the relationship between learning technology and students' writing habits. This study uses a quantitative approach with an online survey data collection technique using the Qualtrics system. The analysis technique used in this study is the Structural Equation Model-Partial Least Square (SEM-PLS). The test results showed that learning technology had a significant influence on writing literacy with a path coefficient of 0.798. This shows that mastery of learning technology provides a positive boost to students' motivation to write. Learning technology on habits and behavior also has a significant direction with a path coefficient of 0.798. The use of technology has increased students' motivation for writing literacy because of the easy access to the necessary resources. Learners feel more motivated to explore new topics and ideas and offer opportunities to express themselves through writing.